ANALISIS PERPINDAHAN PANAS PADA GRATE COOLER INDUSTRI SEMEN - Anwar, Khairil (MEKTEK, 2011)
This research aimed to find out heat transfer rate between cooling air supply and clinker in grate cooler ofcement industry. The method used field survey with two datas. Primary data by direct measure in researchobject and others from control room. Then for the secondary data, we got from manual book of company.Grate cooler was divided into 3 sections, and the analysis performed for each section based on the principleof heat transfer through a porous medium to obtain the heat transfer coefficient, and the rate of heat transfer.Heat transfer of clinker to the cooling air was analyzed by convection and radiation. The result shows thatthe highest convection heat transfer occurs in section 2, while the highest radiation heat transfer occurs insection 1. Total heat transfer in the grate cooler is 95185.936 kW. This result will be smaller than thethermodynamic analysis, with calculation difference of 2%.